2008
DOI: 10.1677/joe-08-0022
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac corticosteroid receptors mediate the enlargement of the ovine fetal heart induced by chronic increases in maternal cortisol

Abstract: Previous studies have demonstrated that modest, physiologically relevant increases in maternal cortisol in late gestation result in enlargement of the fetal heart. In this study, we investigated the role of mineralocorticoid receptor (MR) or glucocorticoid receptor (GR) in this enlargement. Ewes with single fetuses were randomly assigned at w120 days of gestation to one of four groups: maternal cortisol infusion (1 mg/kg per day, cortisol); maternal cortisol infusion with fetal intrapericardial infusion of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
41
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 41 publications
4
41
3
Order By: Relevance
“…The finding that chronic elevation of maternal cortisol dramatically increased the incidence of fetal death and/or stillbirth was unexpected on the basis of our previous studies with shorter (10 -14 days) duration of cortisol infusion ending at 130 days gestation (13,28). Although the cause of fetal demise has yet to be established in these fetuses, there appears to be an association with impaired maternal glucose tolerance and with maternal hyperinsulinemia.…”
Section: Discussionmentioning
confidence: 92%
“…The finding that chronic elevation of maternal cortisol dramatically increased the incidence of fetal death and/or stillbirth was unexpected on the basis of our previous studies with shorter (10 -14 days) duration of cortisol infusion ending at 130 days gestation (13,28). Although the cause of fetal demise has yet to be established in these fetuses, there appears to be an association with impaired maternal glucose tolerance and with maternal hyperinsulinemia.…”
Section: Discussionmentioning
confidence: 92%
“…BMPs are key morphogens regulating the expression of genes involved in organogenesis, including heart development Chen et al, 1997), providing a potential link between GR-mediated cortisol signaling and cardiac morphogenesis. There have been studies linking cortisol to abnormal heart development and cardiac gene expression in fetal sheep (Lumbers et al, 2004;Reini et al, 2008) and to cardiac hypertrophy in adult salmon (Johansen et al, 2011). However, few studies have examined the role of cortisol in the developmental regulation of cardiac function in fish.…”
Section: Introductionmentioning
confidence: 99%
“…We have used an ovine model of chronic maternal stress using exogenous cortisol infusion to increase maternal cortisol concentrations to those comparable to that seen acutely after transport in ewes (31,57). We have found that chronic elevation of maternal cortisol concentrations caused a slowing of overall fetal growth but an increase in fetal heart weight, ventricular wall thickness, and heart weight-tobody weight ratio (28,46). These increases in maternal cortisol produce a modest increase in fetal cortisol relative to the concentrations that are achieved near term, without an increase in fetal blood pressure or an increase in cardiac fibrosis (46).…”
mentioning
confidence: 99%